Regorafenib Suppresses Migration of and Induces Cell Cycle Arrest and Apoptosis in MCF-7 Cells (Brazilian Journal of Pharmaceutical Sciences, 2022)
This study investigated the mechanism underlying the suppression of estrogen receptor-positive MCF7 cell growth by regorafenib. MCF-7 cells were treated with regorafenib, and the effect of regorafenib on multiple cancer-associated pathways was evaluated. Although regorafenib effectively inhibited the proliferation of MCF-7 cells, it had no effect on the proliferation of the normal breast epithelial cell line MCF10A. Regorafenib suppressed MCF-7 cell migration, probably by regulating the homeostatic expression of matrix metalloproteinases and the tissue inhibitor of MMPs. Furthermore, it upregulated p21 expression, downregulated cyclin B1 and cyclin D1 expresssions, and caused cell cycle arrest. In addition, regorafenib induced apoptosis in MCF-7 cells by reducing Mcl-1 expression and activating caspase signaling. These results demonstrate that regorafenib has the potential to be an effective drug for treating breast cancer.